2020
DOI: 10.1007/s00382-020-05125-5
|View full text |Cite
|
Sign up to set email alerts
|

Future projections of wind patterns in California with the variable-resolution CESM: a clustering analysis approach

Abstract: Wind energy production is expected to be affected by shifts in wind patterns that will accompany climate change. However, many questions remain on the magnitude and character of this impact, especially on regional scales. In this study, clustering is used to group and analyze large-scale wind patterns in California using model simulations from the Variable-Resolution Community Earth System Model (VR-CESM). Specifically, simulations have been produced that cover historical , mid-century (2030-2050), and end-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…The dominant patterns that drive winds across Mexico have not previously been explored, whereas these are commonly used in meteorological forecasting in other regions of the (e.g., Bloomfield et al, 2018;Wang et al, 2020). The literature relating to the drivers of weather in the region was summarized by Maldonado et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant patterns that drive winds across Mexico have not previously been explored, whereas these are commonly used in meteorological forecasting in other regions of the (e.g., Bloomfield et al, 2018;Wang et al, 2020). The literature relating to the drivers of weather in the region was summarized by Maldonado et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…We apply EOF combined with the k‐means clustering method to classify WRs in this study. Recently, other classification methods have been proposed, such as support vector regression (Saavedra‐Moreno et al., 2015) and agglomerative clustering algorithms (M. Wang et al., 2020), and studies have demonstrated that both attain a good performance (Saavedra‐Moreno et al., 2015). This study implements one of the main methods, which would be better validated by other methods in the future.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This region of western North America (WNA) contains substantial annual mean wind and solar power resources (Jacobson and Delucchi, 2011;MacDonald et al, 2016;Pryor and Barthelmie, 2011). These resources, however, are subject to substantial seasonal and synoptic variability (Millstein et al, 2019;Rinaldi et al, 2021;Wang et al, 2018;Wang et al, 2020).…”
Section: Spatiotemporal Scale Of Analysismentioning
confidence: 99%